E-Commerce Mobile Based Application Foodienesia - imersto, imersto; Mahendra, Ida Bagus Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Abstr act In this day and age the development of the e-commerce market is increasing. Lots of companies are on the rise, such as gojek, tokopedia, jd.id, lazada, blibli and many others. On the basis of this it is good to learn how to create one of these e-commerce. Because if we see now the e-commerce market is very profitable even arguably more profitable than retail stores. It is possible that in the coming years this e-commerce market will completely outperformed the retail market. From this I saw a huge opportunity from the food industry in Indonesia especially since Indonesia is well known for its food, and I got the idea to create an e-commerce platform that allows someone to buy and sell food online. The platform is "Foodienesia". This platform will allow someone to join to buy and sell food online by using this platform.   Keywords : E-Commerce, Food, Development, Platform, Buy and sell